Assessing the Diversity and Biomedical Potential of Microbes Associated With the Neptune’s Cup Sponge, Cliona patera - Ho, Xin Yi; Katermeran, Nursheena Parveen; Deignan, Lindsey Kane; Phyo, Ma Yadanar; Ong, Ji Fa Marshall; Goh, Jun Xian; Ng, Juat Ying; Tun, Karenne; Tan, Lik Tong (Frontiers in Microbiology, 2021)
Marine sponges are known to host a complex microbial consortium that is essential to the health and resilience of these benthic invertebrates. These sponge-associated microbes are also an important source of therapeutic agents. The Neptune’s Cup sponge, Cliona patera, once believed to be extinct, was rediscovered off the southern coast of Singapore in 2011. The chance discovery of this sponge presented an opportunity to characterize the prokaryotic community of C. patera. Sponge tissue samples were collected from the inner cup, outer cup and stem of C. patera for 16S rRNA amplicon sequencing. C. patera hosted 5,222 distinct OTUs, spanning 26 bacterial phyla and 74 bacterial classes. The bacterial phylum Proteobacteria, particularly classes Gammaproteobacteria and Alphaproteobacteria, dominated the sponge microbiome. Interestingly, the prokaryotic community structure differed significantly between the cup and stem of C. patera, suggesting that within C. patera there are distinct microenvironments. Moreover, the cup of C. patera had lower diversity and evenness as compared to the stem. Quorum sensing inhibitory (QSI) activities of selected sponge-associated marine bacteria were evaluated and their organic extracts profiled using the MS-based molecular networking platform. Of the 110 distinct marine bacterial strains isolated from sponge samples using culture-dependent methods, about 30% showed quorum sensing inhibitory activity. Preliminary identification of selected QSI active bacterial strains revealed that they belong mostly to classes Alphaproteobacteria and Bacilli. Annotation of the MS/MS molecular networkings of these QSI active organic extracts revealed diverse classes of natural products, including aromatic polyketides, siderophores, pyrrolidine derivatives, indole alkaloids, diketopiperazines and pyrone derivatives. Moreover, potential novel compounds were detected in several strains as revealed by unique molecular families present in the molecular networks. Further research is required to determine the temporal stability of the microbiome of the host sponge as well as mining of associated bacteria for novel QS inhibitors.